Perencanaan Pengolahan Limbah Air Wudhu di Masjid Al-Mu’minin Kota Kendari dengan Menggunakan Filtrasi Sederhana - Muh. Anggi Pramoto; Moch. Assiddieq; Rosdiana Rosdiana (Program Studi Teknik Lingkungan, Universitas Muhammadiyah Kendari, 2022)
The large number of Muslim populations in Indonesia cannot be separated from religious activities, one of which is prayer. Before performing prayers, a Muslim first performs ablution using water. With this activity, it will produce a large amount of wastewater in the Al-Mu'minin mosque itself, which can produce ablution water waste of 685.1 L/day with the results of laboratory tests carried out on the quality of groundwater pH 7.84, TSS 38.8 mg/L and turbidity. 6.40 NT in the analysis of the quality of ablution water waste showed that it had exceeded the quality standard, namely TSS 68 mg/L and turbidity was 5 NTU, while the analysis of filtered ablution water waste showed a decrease in levels, namely pH 7.55, TSS 18.70 mg/L and turbidity 3.18 NTU. From the calculation results, the volume of wastewater produced by the mosque is 0.6851 m3/day using a treatment unit in the form of an initial sedimentation tank which has a volume size (Length = 84 cm, Width = 76 cm and Height = 101 cm), a simple filter using media in the form of (Gravel, Sand, Palm Fibers, Charcoal and Sponge) each has a height of 15 cm and the final reservoir has a volume (Length = 84 cm, Width = 76 cm and Height = 101 cm).